The impact of the Work Capability Assessment on mental health: claimants' lived experiences and GP perspectives in low-income communities. (1st October 2019) - Hansford, Lorraine; Thomas, Felicity; Wyatt, Katrina
Abstract : This paper examines the impact of increased welfare conditionality on people with mental health issues claiming benefits in the UK. Drawing on data from the DeStress study, this paper explores the lived experience of welfare claimants in low-income communities, and the perspectives of GPs seeking to support them. Particular focus is placed on people's experience of the Work Capability Assessment, the tool used to determine welfare claimants' entitlement to sickness benefit, and how the narratives and culture surrounding welfare reform and the actual assessment itself can have a negative impact on mental health and wellbeing.